Factors Influencing Online Banking Continuance Intentions Among Older Adults: Evidence from an Emerging Market - Shaun Bvuma; Neo Ligaraba; Pinkie Segodi (Sustainable Business and Society in Emerging Economies, 2025)
Purpose: This study investigates the factors influencing online banking continuance intentions among older adults in South Africa. It focuses on a demographic within an emerging market whose unique challenges and needs remain under investigated. Drawing from existing literature, a research model was developed to examine the proposed relationships between key variables.